2015
DOI: 10.3389/fncel.2015.00465
|View full text |Cite
|
Sign up to set email alerts
|

A Perspective on the Role of microRNA-128 Regulation in Mental and Behavioral Disorders

Abstract: MiRNAs are short, non-coding RNA molecules that regulate gene expression post-transcriptionally. Over the past decade, misregulated miRNA pathways have been associated with various diseases such as cancer, neurodegenerative diseases, and neurodevelopmental disorders. In this article, we aim to discuss the role played by miR-128 in neuropsychiatric disorders, and highlight potential target genes from an in silico analysis of predicted miR-128 targets. We also discuss the differences of target gene determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 81 publications
0
15
1
Order By: Relevance
“…Interestingly, the present data could not corroborate significant differential expression for certain miRNAs previously reported as associated with PDR [25,50,51]. miRNA-29a has been shown to be a negative regulator of DR and its decrease in expression levels is associated with exacerbation of PDR [25,51].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the present data could not corroborate significant differential expression for certain miRNAs previously reported as associated with PDR [25,50,51]. miRNA-29a has been shown to be a negative regulator of DR and its decrease in expression levels is associated with exacerbation of PDR [25,51].…”
Section: Discussioncontrasting
confidence: 99%
“…miRNA-128 regulates multiple pathways within the cell including pathways involved in cancer or neuronal maturation. It has been shown to have tumor suppression activity, and has received particular interest in neuroscience research as it is highly expressed in the cortex and cerebellum during development [50]. Detection of miRNA-128 expression in human vitreous is reported here for the first time, however, its relevance as a biomarker or molecular effector of ocular disease including PDR needs further study.…”
Section: Discussionmentioning
confidence: 84%
“…Besides, our results are consistent with that of Tan and colleagues (Tan et al, ), where miR‐128 was shown to be associated with MAPK and ERK pathways in neurons. Furthermore, Mapk14 has been previously reported to be one of the targets of miR‐128 in neurons (Ching and Ahmad‐Annuar, ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs regulate one‐third of the human genes and thus control a host of cellular functions, that include fundamental processes such as cell differentiation, proliferation and apoptosis, as well as signaling pathways (Croce and Calin, ; Bueno and Malumbres, ; Li et al, ; Su et al, ). miRNA‐128 (miR‐128) is a highly conserved miRNA in human and rodent genomes, suggesting that it may regulate similar cellular functions (Ching and Ahmad‐Annuar, ). Although miR‐128 was identified as a tumor suppressor in breast cancer (Qian et al, ) and lung cancer (Weiss et al, ), nonetheless, it is also a brain‐enriched miRNA (Krichevsky et al, ; Smirnova et al, ), signifying that miR‐128 has diverse roles in human development and disease (Pandey et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation